The existence of Genus Selaginella in Gunung Sibuatan Area, The Nagalingga's Village of Karo District, North of Sumatera|| Keberadaan Selaginella di Kawasan Gunung Sibuatan Desa Nagalingga Kecamatan Merek kabupaten Karo Sumatera Utara - Nasution, Jamilah; Riyanto, Riyanto (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2021)
The Mount Sibuatan area is located in Mark District, Karo Regency, North Sumatra. Selaginella which is located in the Mount Sibuatan area is at an altitude of 1550 mdpl-2236 mdpl which has high enough humidity which is a suitable habitat for Selaginella to grow. The purpose of this study was to identify the type of Selaginella found in the Mount Sibuatan area, Brand District, Karo Regency, North Sumatra. The research method used is descriptive with sampling using target sampling with exploratory techniques. The results of the study found 4 species consisting of; Selaginella intermedia (terrestrial, erect, creeping), Selaginella subalpina (terrestrial, erect), Selaginella opaca (terrestrial, epilytic, creeping) and Selaginella s.p (terrestrial, epilytic, creeping). The highest species abundance of Selaginella found were Selaginella Intermedia, this species found at an altitude of 1550 m above sea level, with environment of pH level 5.4 and temperature of 18Â°C. Selaginella subalpina that as the lowest abundance found at an altitude of 1550 meters above sea level, with environment of pH level 7.0 and temperature of 18°C.Kawasan Gunung Sibuatan berada pada Kecamatan Merek Kabupaten Karo, Sumatera Utara. Selaginella yang berada di kawasan Gunung Sibuatan berada di ketinggian 1550 mdpl- 2236 mdpl yang memiliki kelembapan cukup tinggi yang merupakan habitat yang cocok sesuai dengan pertumbuhan Selaginella. Tujuan dari penelitian ini untuk mengetahui jenis-jenis Selaginella yang berada di kawasan Gunung Sibuatan Kecamatan Merek Kabaputen Karo, Sumatera Utara. Metode penelitian yang digunakan yaitu deskriptif dengan pengambilan sampel dengan menggunakan purposive sampling dengan tekhnik ekplorasi. Hasil penelitian ditemukan 4 jenis terdiri dari; Selaginella Intermedia (teresterial tegak, menjalar), Selaginella subalpina (teresterial. tegak), Selaginella opaca (teresterial, epilitik, menjalar), dan Selaginella sp (teresterial, epilitik, menjalar).